(untitled) (Heritage, 2020)
The first History of Serbian Literature (1865) was written from the pen of P. J. Safarik (1796-1861), a foreigner, who lived and worked in Novi Sad and did not write in Serbian. The final form was given by Safarik’s son-in-law, who made some changes. The first edition was printed in 1826. The monograph includes a review of 289 writers. In addition to Serbian, he also deals writers who have written in foreign languages. The book contain a list of printers, patrons, scribes, a Cyrillic print of Catholic Serbs and a Cyrillic print of Protestants. He deals with works in the field of language science, rhetoric and poetry, philosophy, history and geography, pedagogy and mathematics, science of nature and technology, medicine, law and politics, including works in the field of theology. It is, therefore, a project that, through its critique of literature, actually illuminates the history of the culture of the Serbian people. Methodologically History is realized as it is done by contemporary historians of literature. Safarik’s critical method, is proof that literary criticism always has a social function, if it is scientifically based and objective. Key words: history of literature, Pavel Jozef Shafarik, literary criticism, culture, society.